2008
DOI: 10.1029/2007jb004958
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow study at the Chinese Continental Scientific Drilling site: Borehole temperature, thermal conductivity, and radiogenic heat production

Abstract: [1] The Chinese Continental Scientific Drilling (CCSD) Project offers a unique opportunity for studying the thermal regime of the Dabie-Sulu ultrahigh-pressure metamorphic belt. In this paper, we report measurements of borehole temperature, thermal conductivity, and radiogenic heat production from the 5158 m deep main hole (CCSD MH). We have obtained six continuous temperature profiles from this borehole so far. The temperature logs show a transient mean thermal gradient that has increased from 24.38 to 25.28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…The less time-consuming optical scanning technique (OS) is, since introduced in the 1990s by Y. Popov, recently the most frequently used method to measure TC for large sample sets. This method was applied successfully to crystalline rocks (e.g., He et al, 2008;Popov et. al., 1999) as well as to sedimentary rocks (e.g., Clauser, 2006;Fuchs and Förster, 2010;Hartmann et al, 2005Hartmann et al, , 2008Homoth et al, 2008;Liu et al, 2011;Majorowicz et al, 2008;Mottaghy et al, 2005;Norden and Förster, 2006;Orilski et al, 2010;Popov et al, 1995Popov et al, , 2003Popov et al, , 2010Popov et al, , 2011Schütz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The less time-consuming optical scanning technique (OS) is, since introduced in the 1990s by Y. Popov, recently the most frequently used method to measure TC for large sample sets. This method was applied successfully to crystalline rocks (e.g., He et al, 2008;Popov et. al., 1999) as well as to sedimentary rocks (e.g., Clauser, 2006;Fuchs and Förster, 2010;Hartmann et al, 2005Hartmann et al, , 2008Homoth et al, 2008;Liu et al, 2011;Majorowicz et al, 2008;Mottaghy et al, 2005;Norden and Förster, 2006;Orilski et al, 2010;Popov et al, 1995Popov et al, , 2003Popov et al, , 2010Popov et al, , 2011Schütz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the line-source method of Horner (1951), as implemented by Lachenbruch and Brewer (1959), is relatively precise even though it does contain an inherent bias to lower temperatures that reduces accuracy slightly (Beardsmore and Cull, 2001). A detailed study describing the proper application of this method has recently been reported by He et al (2008).…”
Section: Temperature Logs and Geothermal Gradientmentioning
confidence: 99%
“…Since the 1990s, the optical scanning technique [15] was widely applied to measurements of rock thermal conductivity, which has advantages such as high work efficiency, non contact manner, direct measurements on rock-cores (no need to make samples) and being able to estimate anisotropy and inhomogeneity of rocks. So far the successful cases of its utility includes the Vorotilovo deep borehole at the East Europe platform [28] , deep borehole at the Kola peninsula of Russia [29] , and deep borehole at the Sulu-Dabie area of China [30] .…”
Section: Measurement Methods Of Rock Thermal Conductivitymentioning
confidence: 99%